Terapi Non-Invasive Continuous Positive Airway Pressure (CPAP) Ventilation pada Keracunan Gas Karbon Monoksida - Dedy Kristofer Simangunsong; Septo Sulistio; Eirene Simbolon; Erwin Kristianto Simangunsong (Cermin Dunia Kedokteran, 2024)
Carbon monoxide (CO) poisoning is one of the leading environmental emergencies with high mortality and morbidity. The brain and heart are especially at-risk organs of being affected. Clinical manifestations may closely mimic various nonspecific viral illnesses. Diagnosis is made based on of clinical symptoms, patient history, and the location’s circumstances. Current therapy recommendations for CO poisoning are 100% normobaric oxygen (NBO) or hyperbaric oxygen (HBO). Non-invasive ventilation CPAP (continuous positive airway pressure) method is effective as a therapy for CO poisoning in the emergency room because it can provide tissue oxygenation and eliminate CO quickly.